2018
DOI: 10.1039/c8ra02241k
|View full text |Cite|
|
Sign up to set email alerts
|

Highly porous core–shell chitosan beads with superb immobilization efficiency forLactobacillus reuteri121 inulosucrase and production of inulin-type fructooligosaccharides

Abstract: With the aim to overcome the limitations of hydrogel chitosan beads (HGBs), various types of chitosan, core-shell chitosan beads (CSBs), and dried chitosan beads (DBs) were synthesized. Physical and chemical properties were compared with those of HGBs. CSBs were proved to be an effective support because they displayed higher stability and capacity over the HGBs, and thus, were selected for enzyme

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
2
12
0
1
Order By: Relevance
“…The reduction of CLEA activity in early cycles might result from the more compact nature of CLEAs or desorption of non-covalently bound enzyme molecules after recycling of the biocatalyst. This phenomenon was also found in other covalent-immobilized enzymes, such as levansucrase immobilized on vinyl sulfone-activated silica [40] and inulosucrase immobilized on core-shell chitosan beads [25].…”
Section: Operational Stability Of R483a-lrinu Cleassupporting
confidence: 64%
See 1 more Smart Citation
“…The reduction of CLEA activity in early cycles might result from the more compact nature of CLEAs or desorption of non-covalently bound enzyme molecules after recycling of the biocatalyst. This phenomenon was also found in other covalent-immobilized enzymes, such as levansucrase immobilized on vinyl sulfone-activated silica [40] and inulosucrase immobilized on core-shell chitosan beads [25].…”
Section: Operational Stability Of R483a-lrinu Cleassupporting
confidence: 64%
“…Many studies have revealed that this method can be applied to a broad range of carbohydrate-modifying enzymes, for instance α-amylase [22], β-galactosidase [23], and levansucrase [24]. Nevertheless, to the best of the authors' knowledge, only our work has reported on IFOs synthesis using an immobilized inulosucrase [25] and no reports have been made on the preparation of CLEAs of inulosucrase. To fully understand the potential application of the different forms of immobilized inulosucrase for IFOs synthesis, further studies are required.…”
Section: Of 12mentioning
confidence: 96%
“…The production of inulin and levan has not reached industrial levels; however, they can both be produced by either fermentation or enzymatic systems (via inulosucrases), using sucrose as an acceptor (Porras-Domínguez et al, 2014;Mensink et al, 2015;Ni et al, 2018). Inulin synthesis via inulosucrases has been reported for LAB species such as Lactobacillus gasseri DSM 20604 (Ni et al, 2018), Lactobacillus reuteri 121 (Charoenwongpaiboon et al, 2018), Lactobacillus jensenii JV-V16 (Ni et al, 2020), Lactobacillus johnsonii NCC533 (Saadat et al, 2019), Leuconostoc citreum CW28 (Saadat et al, 2019), and Streptococcus mutans (Saadat et al, 2019). In the particular case of inulin synthesis by Lactobacillus jensenii JV-V16, the yield of inulin obtained (278 g/L) is high, showing its capability to be applied in industrial-scale processes; however, it is important to note that the enzyme was overexpressed using molecular biology (Ni et al, 2020).…”
Section: Inulin and Levan Productionmentioning
confidence: 99%
“…Beyond technological applications mentioned in this session, hydrogel and nanocomposites based on CS and their derivatives have been studied for other several applications, such as contact lenses [238,239], enzyme and cell separations and immobilizations [71,[240][241][242][243], DNA delivering [244], cartilage and skin regenerations [245][246][247][248][249], biosensors [250][251][252], submucosal fluid or injections [253][254][255][256][257], tissue engineering [258][259][260][261][262][263], postoperative adhesion prevention [264][265][266], cancer treatment [267][268][269][270], orthopedic applications [271,272], artificial muscles [273], and others. Important characteristics of some cited applications are discussed as follows.…”
Section: Other Technological Applicationsmentioning
confidence: 99%